STUDI TEKNIK PENGOPERASIAN PANCING ULUR CUMI DAN HASIL TANGKAPAN DI PERAIRAN ARAFURA - Noventius Manek; Samudra Alfatiha; Martobi Ndolu; Donisius Prawira Hidayat; Rahmat Suhada Lawang; I Putu Sugiana (Universitas Mataram, 2026)
Arafura waters are one of the main squid (Loligo sp.) fishing areas in Indonesia with an important contribution to national capture fisheries production. This study aims to describe the squid handline operation technique and analyze the types and quantities of catches on KM. Bandar Nelayan 118 based in Benoa Harbor, Bali. The study was conducted in October–November 2023 through direct observation on board, interviews with the captain and crew, and documentation of fishing activities. Data were analyzed descriptively qualitatively. The results showed that squid handline operations were carried out at night with the help of 2000 watt metal halide lamps, using four main techniques, namely bottom fishing (ahe-ahe), mid-line fishing (kokokan), surface fishing (lempang), and sate fishing. Fishing gear is selective and only catches Loligo sp. squid without bycatch. The total catch during the study reached approximately 9,902 kg, with daily fluctuations influenced by currents, baiting techniques, bait color, and the location of the catch. This study demonstrates that squid handline fishing on the KM. Bandar Nelayan 118 is effective, selective, and has the potential to support sustainable capture fisheries in the Arafura Waters.